Zakat in the perspective of qur'an interpretation and sharia economics: a strategic role in poverty alleviation and MSME empowerment - Hermansyah, Hermansyah (Jurnal Konseling dan Pendidikan, 2025)
Zakat is a fundamental pillar of Islamic economics, serving as a vital instrument for wealth redistribution and poverty alleviation. Its significance aligns closely with the United Nations Sustainable Development Goals (SDGs), particularly SDG 1 on poverty eradication and SDG 10 on reducing inequality. This study employs a mixed-methods approach, combining Qur'anic exegesis of Surah At-Tawbah verse 60 with empirical data from Indonesia’s National Amil Zakat Agency (BAZNAS) 2024 report. The findings reveal a substantial gap between the national zakat potential, estimated at approximately Rp327 trillion annually, and the actual collection, which stands at only Rp26.13 trillion, representing about 8% realization. Despite this gap, productive zakat programs have demonstrated significant socio-economic impact, increasing MSME incomes by up to 40% over two years and contributing to a 1.76% reduction in poverty rates within targeted communities. The study recommends enhancing zakat collection through digitalization and integrating zakat management with national social protection programs to maximize its effectiveness. These strategies are essential to harnessing zakat’s full potential as a socio-economic tool for inclusive and sustainable development in Indonesia.